Selected amino acid mutations in HIV-1 B subtype gp41 are Associated with Specific gp120V3 signatures in the regulation of Co-Receptor usage - D'Arrigo Roberta; Svicher Valentina; Mercurio Fabio; Dimonte Salvatore; Perno Carlo-Federico; Ceccherini-Silberstein Francesca (Retrovirology, 2011)
Abstract Background The third variable loop (V3) of the HIV-1 gp120 surface protein is a major determinant of cellular co-receptor binding. However, HIV-1 can also modulate its tropism through other regions in gp120, such as V1, V2 and C4 regions, as well as in the gp41 protein. Moreover, specific changes in gp41 are likely to be responsible for of damage in gp120-CCR5 interactions, resulting in potential resistance to CCR5 inhibitors. In order to genetically characterize the two envelope viral proteins in terms of co-receptor usage, we have analyzed 526 full-length env sequences derived from HIV-1 subtype-B infected individuals, from our and public (Los Alamos) databases. The co-receptor usage was predicted by the analysis of V3 sequences using Geno2Pheno (G2P) algorithm. The binomial correlation phi coefficient was used to assess covariation among gp120V3 and gp41 mutations; subsequently the average linkage hierarchical agglomerative clustering was performed. Results According to G2P false positive rate (FPR) values, among 526 env-sequences analyzed, we further characterized 196 sequences: 105 with FPR <5% and 91 with FPR >70%, for X4-using and R5-using viruses, respectively. Beyond the classical signatures at 11/25 V3 positions (S11S and E25D, R5-tropic viruses; S11KR and E25KRQ, X4-tropic viruses), other specific V3 and gp41 mutations were found statistically associated with the co-receptor usage. Almost all of these specific gp41 positions are exposed on the surface of the glycoprotein. By the covariation analysis, we found several statistically significant associations between V3 and gp41 mutations, especially in the context of CXCR4 viruses. The topology of the dendrogram showed the existence of a cluster associated with R5-usage involving E25DV3, S11SV3, T22AV3, S129DQgp41 and A96Ngp41 signatures (bootstrap = 0.88). Conversely, a large cluster was found associated with X4-usage involving T8IV3, S11KRV3, F20IVYV3, G24EKRV3, E25KRV3, Q32KRV3, A30Tgp41, A189Sgp41, N195Kgp41 and L210Pgp41 mutations (bootstrap = 0.84). Conclusions Our results show that gp120V3 and several specific amino acid changes in gp41 are associated together with CXCR4 and/or CCR5 usage. These findings implement previous observations that determinants of tropism may reside outside the V3-loop, even in the gp41. Further studies will be needed to confirm the degree to which these gp41 mutations contribute directly to co-receptor use.